2008
DOI: 10.1136/jnnp.2008.144501
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diagnosis with follow-up in an incident cohort of patients with parkinsonism

Abstract: Background: Accurate diagnosis of the cause of parkinsonism during life can be difficult, particularly at presentation, but few studies have described changes in clinical diagnosis over time and the effect of applying strict research criteria. Methods: Incident patients with a possible/probable diagnosis of degenerative or vascular parkinsonism had a standardised assessment at diagnosis and at yearly intervals thereafter at which the most likely clinical diagnosis was recorded without strict application of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 30 publications
4
26
0
5
Order By: Relevance
“…First, the implications of a novel genetic variant are particularly difficult to define (MacArthur et al 2014). The clinical phenotype often does not correspond to the anticipated neuropathology, and specific disease alleles are associated with a wide phenotypic spectrum (Caslake et al 2008;GrauRivera et al 2015). This makes it extremely difficult to establish whether a novel genetic variant is responsible for the disorderan issue that is gaining importance, given the widespread use of clinical exome and genome sequencing.…”
mentioning
confidence: 99%
“…First, the implications of a novel genetic variant are particularly difficult to define (MacArthur et al 2014). The clinical phenotype often does not correspond to the anticipated neuropathology, and specific disease alleles are associated with a wide phenotypic spectrum (Caslake et al 2008;GrauRivera et al 2015). This makes it extremely difficult to establish whether a novel genetic variant is responsible for the disorderan issue that is gaining importance, given the widespread use of clinical exome and genome sequencing.…”
mentioning
confidence: 99%
“…6 Currently, a diagnosis is made based on clinical findings, and autopsy studies estimate the clinical diagnostic accuracy for PD ranges from 46% to 90%. [7][8][9][10][11] While autopsy findings of Lewy bodies in the substantia nigra remains the gold standard for diagnosis, a postmortem survey of Lewy type a-synucleinopathy (LTS) in the peripheral nervous system (PNS) 12 found a rostral caudal gradient from the lower esophagus and submandibular gland to the colon and rectum. 12 In a postmortem study of 28 PD cases, LTS was found in all 28 whole block mounts of the submandibular gland.…”
mentioning
confidence: 99%
“…It is clear that accuracy of the clinical diagnosis of PD improves in more advanced disease. [7][8][9][10][11] Depending on the criteria used for the diagnosis, many cases may not have a striatal dopaminergic deficit and many will have non-PD parkinsonism due to other neurodegenerative disorders such as progressive supranuclear palsy, multiple system atrophy, and corticobasal degeneration. Given the results in this study, future studies with patients with shorter disease duration will be important as having an accurate tissue diagnosis in patients with early PD would greatly increase the probability for successful clinical trials and provide tissue confirmation for other biomarker studies.…”
mentioning
confidence: 99%
“…One objective of noninvasive neuroimaging techniques in PD is to find markers that aid in the diagnosis, disease-progression monitoring, and long-term drug-impact evaluation. 1 MR imaging with rich tissue contrasts and high spatial resolution offers a unique value for probing PD brain structure and function. Particularly, there has been substantial interest in in vivo MR imaging of increased nigral iron content, 2,3 a pathophysiologic feature involved in the selective dopaminergic neurodegeneration of the substantia nigra in patients with PD.…”
mentioning
confidence: 99%